MODIFICATION OF GEOLOGICAL ENVIRONMENT OF YEREVAN CITY UNDER THE TECHNOGENIC IMPACT (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
In this article natural conditions of Yerevan City, modification of geological environment under the influence of technogenic impacts are considered. Development of industry and construction causes uncontrolled modifications of ground water regime, as well as activation of landslides, collapses, subsidence of soils. Zoning of territory of the city on modification of geological environment has been carried out. In greatly altered territories conducting of drainage channels, restoration of irrigative, water supply-sewer nets, meliorating of waste disposal territories are recommended.
Keywords: technogenic impacts; uncontrolled modifications of ground water regime